2017
DOI: 10.1049/hve.2017.0066
|View full text |Cite
|
Sign up to set email alerts
|

Translational plasma stomatology: applications of cold atmospheric plasmas in dentistry and their extension

Abstract: In recent years, translational plasma medicine (TPM), as a novel application area of plasmas, has attracted much attention of experts from both academic and clinical fields. State-of-the-art of the lab-scale research and clinical trials of the cold atmospheric plasmas (CAPs) in the stomatology are reviewed in detail from the direct and indirect applications of the CAPs. Based on the discussions concerning the relationship between the plasma stomatology and the plasma medicine, it is indicated that it would be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 141 publications
(192 reference statements)
0
26
0
Order By: Relevance
“…As the fourth state of matter [1], plasma plays an increasingly important role in our daily life and scientific progress, such as for medical application, surface modification and environmental pollution control etc. [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As the fourth state of matter [1], plasma plays an increasingly important role in our daily life and scientific progress, such as for medical application, surface modification and environmental pollution control etc. [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Cold atmospheric plasmas (CAPs) have attracted much attention from researchers due to their unique features, such as low gas temperatures, abundant chemically reactive species and flexible operations with the removal of vacuum system, and have bright application prospects in the fields of bio-medicine, advanced materials synthesis and modifications, energy saving and environmental protection, etc. Among the preceding CAP applications, biological and medical applications of the CAPs have become one of the research focuses in the interdisciplinary fields of plasma physics and chemistry, biochemical engineering, medical science and clinical operations [1][2][3]. As one of the most three promising application fields in plasma medicine at the present time, i.e., cancer therapy, dermatology and stomatology, study of the CAPs in dentistry can also be regarded as a miniature of the plasma medicine, including indirect applications of CAPs for the surface modifications of biomedical materials, and direct applications of CAPs for the medical therapy [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Among the preceding CAP applications, biological and medical applications of the CAPs have become one of the research focuses in the interdisciplinary fields of plasma physics and chemistry, biochemical engineering, medical science and clinical operations [1][2][3]. As one of the most three promising application fields in plasma medicine at the present time, i.e., cancer therapy, dermatology and stomatology, study of the CAPs in dentistry can also be regarded as a miniature of the plasma medicine, including indirect applications of CAPs for the surface modifications of biomedical materials, and direct applications of CAPs for the medical therapy [2,3]. Recent studies have shown that the CAP treatment can be regarded as an effective and clean method for producing the micro-or nanoscale structures on the biomaterials or implants [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It also can be classified according to their parameters. At atmospheric pressure level, there is a thermal type and cold plasma (non-thermal) with gas temperature close to room temperature (11) .…”
Section: Introductionmentioning
confidence: 99%